2016
DOI: 10.1104/pp.16.00937
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Phthalimide AC94377 Is a Selective Agonist of the Gibberellin Receptor GID1

Abstract: ORCID IDs: 0000-0001-9901-5293 (K.J.); 0000-0003-0774-6203 (T.A.).Gibberellin (GA) is a major plant hormone that regulates plant growth and development and is widely used as a plant growth regulator in agricultural production. There is an increasing demand for function-limited GA mimics due to the limitations on the agronomical application of GA to crops, including GA's high cost of producing and its leading to the crops' lodging. AC94377, a substituted phthalimide, is a chemical that mimics the growth-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This accumulated evidence has resulted in the development of agonists and antagonists targeting phytohormone receptors. 96,[119][120][121] In the example of ABA receptors, ABA analogs have been designed as antagonists of ABA co-receptor interactions based on their structure. 122) The structures of some redundant ABA receptors complexed with pyrabactin also demonstrated the structural basis of why the synthetic chemical activates only a subset of the receptors, such as PYR1 and PYL1, leading to the development of quinabactin, which activates a broader range of ABA receptors than pyrabactin to effectively promote drought resistance in plants as ABA does.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This accumulated evidence has resulted in the development of agonists and antagonists targeting phytohormone receptors. 96,[119][120][121] In the example of ABA receptors, ABA analogs have been designed as antagonists of ABA co-receptor interactions based on their structure. 122) The structures of some redundant ABA receptors complexed with pyrabactin also demonstrated the structural basis of why the synthetic chemical activates only a subset of the receptors, such as PYR1 and PYL1, leading to the development of quinabactin, which activates a broader range of ABA receptors than pyrabactin to effectively promote drought resistance in plants as ABA does.…”
Section: Discussionmentioning
confidence: 99%
“…This selectivity is attributed to a single residue at the GA-binding pocket of AtGID1s (AtGID1a V319 and ATGID1c I317). 96) These findings suggest a complicated manner of the growth and development through the interaction between GID1 and DELLA in Arabidopsis. Similar receptor diversity has been reported on three JA receptor COI1 in rice (OsCOI1a, OsCOI1b, and OsCOI2) although Arabidopsis genome has a single copy of COI1 gene.…”
Section: Molecular Diversity Of Phytohormone Receptorsmentioning
confidence: 92%
“…Being a highly promising seed germination regulator, the mode of AC-94377 functioning was deeply analyzed. Despite the structural differences between GA3 and AC-94377, Jiang et al (2017) demonstrated that AC-94377 binds to the At-GID 1, an Arabidopsis GA receptor. Table 1 The list of compounds promoting seed germination of barley and other plant species.…”
Section: Phthalimidesmentioning
confidence: 94%
“…The primers for PCR, AtGA3ox1, AtEXP1 (encoding expansin1) and AtACT7 (encoding actin7) were used as described previously. 20) OsGA20ox2, OsGA2ox4 (Os05g0514600), and the housekeeping gene OsACT1 (encoding actin1) were amplified with the following primers: OsGA20ox2-forward (5′-GCCAATGGGGAGGG TGT-3′) and -reverse (5′-CCATGATCGTCAGCGACA-3′), OsGA2ox4-forward (5′-AGGAGCTTGCTTCCAAC AAAG-3′) and -reverse (5′-CAACAGGTTTCCCAA-CACTG-3′), and OsACT1-forward (5′-TGGCATCTCT-CAGCACATTCC-3′) and -reverse (5′-TGTGCACAAT GGATGGG-3′).…”
Section: Real-time Rt-pcr Analysismentioning
confidence: 99%
“…Docking simulation analysis of interactions between H-acid and OsGID1 was performed with Chimera and AutoDock Vina based on the data for 3EBL from the Protein Data Bank as described previously. 20) Results GA-like activity of H-acid in rice and Arabidopsis GA-like activities of H-acid have been demonstrated in many plants such as rice, grass, and tobacco. [10][11][12]…”
Section: Molecular Dockingmentioning
confidence: 99%